Health status in gilthead seabream (Sparus aurata) juveniles fed diets devoid of fishmeal and supplemented with Phaeodactylum tricornutum - Reis, B. (2021)
To enhance fish general health, feeds can be supplemented with health-promoting additives, reducing the need to use chemotherapeutics. Incorporation of marine algae biomasses in aquafeeds has been shown to improve fish immune status by enhancing innate immune response. This study evaluated the effects of Phaeodactylum tricornutum incorporation in feed by two different processes, either as freeze-dried biomass or broken cell wall biomass, on fish health status and performance. Triplicate groups of gilthead seabream juveniles (13.3 +/- 0.3 g) were either fed a control diet (CTRL) with an extreme (i.e., 0% fishmeal), nutritionally balanced, formulation, or two experimental diets formulated as the CTRL with 1% inclusion of the microalga P. tricornutum at the expense of wheat meal: BC diet contains P. tricornutum broken cells and WC diet microalgae whole cells. After 2 and 12 weeks of feeding, blood was collected for hematological procedures, whereas plasma and mucus were sampled for immune parameters. Head-kidney, liver, and white skeletal muscle were also collected for gene expression measurements. No major differences were observed in hematological nor plasma humoral parameters after 12 weeks irrespective of dietary treatment. Arrays of 29-31 genes were analyzed in the different tissues, revealing an early dietary effect (2 weeks) in a tissue-specific pattern. In the liver, the major effect was found in the GH/IGF axis and in muscle there was a late downregulation of myostatin (mstn) gene, mainly due to WC diet, even though all fish had similar growth performance. Regarding the head-kidney, BC diet led to alpha-2-macroglobulin (a2m) gene upregulation. Also, the same treatment showed increased mucus alternative complement pathway and bactericidal activity at 2 and 12 weeks, respectively. Hence, it seems that BC diet has a potential stimulatory effect that might be relevant as a prophylactic measure before a predictable stressful event.